Tracing the formation history of intermediate-age star clusters in the Small Magellanic Cloud - Piatti, Andres Eduardo (2005)
Colour–magnitude diagrams (CMDs) are presented for the first time for 10 star clusters projected on to the Small Magellanic Cloud (SMC). The photometry was carried out in the Washington system C and T1 filters allowing the determination of ages by means of the magnitude difference between the red giant clump and the main-sequence turnoff (MSTO), and metallicities from the red giant branch (RGB) locus. The clusters all have ages in the range 1.5–4 Gyr and metallicities between −1.3 < [Fe/H] < −0.6, with respective errors of ∼0.5 Gyr and 0.3 dex. This increases substantially the sample of intermediate-age clusters in the SMC with well-derived parameters. We combine our results with those for other clusters in the literature to derive as large and homogeneous a data base as possible (totalling 26 clusters) in order to study global effects. We find evidence for two peaks in the age distribution of SMC clusters, at ∼6.5 and 2.5 Gyr, in good agreement with previous hints involving smaller samples. The most recent peak occurs at a time that corresponds to a very close encounter between the Large Magellanic Cloud (LMC) and the SMC according to the recent dynamical models of Bekki et al. that they used to explain the enhancement of LMC clusters with this age. It appears cluster formation may have been similarly stimulated in the SMC by this encounter as well. We also find very good agreement between cluster ages and metallicities and the prediction from a bursting model from Pagel and Tautvaišienė with a burst that occurred 3 Gyr ago. These two lines of evidence together favour a bursting cluster formation history as opposed to a continuous one for the SMC.